Transforming usury into finance: Financialization and the ethics of debt - Kate Padgett Walsh (Finance and Society, 2018)
This article examines the conceptual transformation of what was once considered usury into finance. To counter traditional arguments that usury was exploitative and unnatural, early modern theorists reconceptualized debt as a form of investment for both borrowers and lenders. Today, this ethical justification of debt as an investment underlies the rhetoric of finance and financialization. Close examination of the realities of contemporary financialized debt, however, reveal that much of this rhetoric is misleading and false. While the rhetoric of finance is unrelentingly oriented toward the future, the lived reality of debt is one of being constrained and haunted by the past. Relatedly, this rhetoric exhorts borrowing for investment, while finance has actually had the opposite effect of making consumer debt a necessity for the majority of Americans. Taken together, these realities of debt today contradict the rhetoric of finance as investment and undermine the ethical framework on which it depends.
Keywords: 300; Ethics; usury; debt; finance; rhetoric; investment